2007
DOI: 10.1016/j.bcp.2007.04.012
|View full text |Cite
|
Sign up to set email alerts
|

The inhibitors of protein acylation, cerulenin and tunicamycin, increase voltage-dependent Ca2+ currents in the insulin-secreting INS 832/13 cell

Abstract: As it has been suggested that protein acylation plays a role in nutrient stimulus-secretion coupling in the pancreatic β-cell, we examined the insulin secreting INS 832/13 β-cell line for evidence that protein acylation was involved. The perforated whole-cell configuration was employed to voltageclamp INS 832/13 cells. Voltage pulses were applied and Ca 2+ -currents measured in the presence and absence of the protein acylation inhibitors cerulenin and tunicamycin. Both inhibitors enhanced the peak amplitude of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…Although our data demonstrate involvement of mitochondrial dysfunction in palmitate-induced GSIS impairment, palmitate also likely acts on non-mitochondrial processes relevant to GSIS, e.g. K ATP channel closure [41], Ca 2+ channel opening [42] and exocytosis [43]. Attenuation of KCl-induced insulin release by palmitate (Fig.…”
Section: Mitochondrial Dysfunction Contributes To Palmitate-induced Gmentioning
confidence: 81%
“…Although our data demonstrate involvement of mitochondrial dysfunction in palmitate-induced GSIS impairment, palmitate also likely acts on non-mitochondrial processes relevant to GSIS, e.g. K ATP channel closure [41], Ca 2+ channel opening [42] and exocytosis [43]. Attenuation of KCl-induced insulin release by palmitate (Fig.…”
Section: Mitochondrial Dysfunction Contributes To Palmitate-induced Gmentioning
confidence: 81%
“…The apparent additivity of short-term/acute GLT stress with PAK1 knockdown could suggest that GLT induces an early PAK1-independent signal that is insufficient to evoke cell death; since PAK1 levels are un-impacted by this, the anti-apoptotic mechanism is maintained. Indeed, acute GLT treatment impacts K ATP and Ca 2+ channel functions in beta cells without inducing apoptosis [27, 28]. However, once GLT exposure is prolonged, then PAK1 is decreased, and ERK1/2 and Bcl2 are left unchecked to allow apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…Among numerous possible protein targets for acylation in the β-cell are ion channels (Gubitosi-Klug et al 2005; Hurley et al 2000), G-proteins (Cao and Huang 2005), receptors (Tobin and Wheatley 2004) and SNARE proteins (Roth et al 2006) that are implicated in stimulus secretion coupling. In this regard we found that two inhibitors of protein acylation, cerulenin and tunicamycin, both increase Ca 2+ currents through L-type voltage-dependent Ca 2+ channels in the INS 832/13 cells (Zhao et al 2007) showing that protein acylation is attenuating the responsiveness of these channels. Additionally, we have provided evidence that protein acylation may be involved in the mechanisms of inhibition of insulin secretion by the physiological inhibitors norepinephrine, somatostatin, galanin and PGE 2 (Cheng et al 2003).…”
Section: Discussionmentioning
confidence: 89%